INTOXICATION PAR LA CHLOROqUINE Chloroquine intoxication - MÉGARBANE, Bruno (Mediterranean Journal of Emergency Medicine, 2021)
Chloroquine poisoning is rare but may be life-threatening. Toxicity results from membrane stabilizing effect related to the blockage of sodium channels on myocardial contractile cells and conduction tissue. Bad prognosticators include the presumed ingested dose >4 g, the decrease in systolic blood pressure <100 mmHg, and the enlargement of QRS >0.10 s on the electrocardiogram. In the emergency department and even as soon as at the pre-hospital scene, management relies on tracheal intubation, epinephrine and diazepam infusion in severely poisoned patients, based on prognosticators, in order to prevent the onset of cardiac complications.